Tribological behavior of waste cooking oil blended lubricant - Sakinah, Muhamad Hisham (2017)
In the current decade, the development of renewable products to replace fossil products is an essential and important issue from industrial, environment, and academic point of views. In the current study, an attempt was made to study the tribological behaviour of waste cooking oil blended with SAE 40, investigate their viscosity and moisture content and also optimized the differemt operating parameter of the tribological performance. Waste cooking palm oil (WCO) was chosen from the most common waste oil using in Malaysia. Waste cooking oil was undergone three types of process, the coarse filtering, dewatering and fine filtering. Moisture content and viscosity analysis were investigated to study the physical properties of blended lubricant as well as the effectiveness of filtration method. Wear and friction performance was evaluated using piston-liner contact tester, and the material use is aluminium 6061 which is the standard material for piston. The design of experiment (DOE) was constructed using Response Surface Methodology (RSM) method. Influence of different operating parameter such as rotational speeds (200 RPM,250 RPM, 300 RPM), volume concentration (SAE 40, 5% and 10% of waste oil), and applied loads (2 kg, 5.5kg and 9kg) investigated and obtain the optimization for different lubricant in tribological behavior. Field Emission Scanning Electron Microscope (FESEM) that equipped with EDX system was used to identify the wear mechanism and element on the surface of the specimen. According to the coefficient of friction versus time result and the weight loss result, the friction coefficient between the three concentrations of oil shows a considerable difference between SAE 40 and two blended lubricant. Based on the properties result, for viscosity, as the concentration of waste cooking oil increases, the viscosity of the bio-lubricant decreases. According to result in moisture content, the moisture content percentage in 0% volume concentration of waste cooking oil is the same with moisture content percentage in 10% volume concentration of waste cooking oil while 5% shows the lowest percentage of the moisture content. Based on SEM result, the wear on the surface specimen decrease as the concentration of waste cooking oil added with engine oil reduce, and it was due to the SAE 40 showed the highest viscosity result compared to 10% concentration because higher viscosity tends to drag the movements between two contact surfaces. It can be said that using a small amount of WCO in the engine oil was not give much impact in the engine component regarding on their coefficient of friction and wear mechanism. From the lubricant properties analysis, it shows that the properties of the blended lubricant approached with the lubricant baseline (SAE 40).